Blockchain-based Storage with SGX Clients for Mobile Games - Cardoso, Rodrigo Martins (2020)
In the last years, many mobile multiplayer games with a large number of users have become popular and a prime example of this is the Pokémon GO. These planetary-scale games are truly engineering challenges requiring a decentralized architecture to support the traffic of thousands of players. The recent and continuous technological advances of mobile devices allow us to build smartphones with better computing, storage and graphics power which attracts an exorbitant number of players globally. By combining all the functionalities available in this type of device (touch screen, motion sensor, precise location system, etc.) with the ubiquitous connection to the network online games connected to device movement, multiplayer games, location based games and application stores are possible. With all these capabilities together, smartphone games deliver a distinct user experience and open up a horizon of unexplored possibilities. With the expansion of the number of mobile users, the proliferation of smartphones and tablets, and the growing interest in mobile multiplayer games, a growing demand for services, technologies and architectures to support wireless gaming inevitably arises to address the difficulty of supporting such mass-scale games in a centralized fashion. As an innovative solution to this demand, a model was designed that allows mobile clients to communicate with strong guarantees, to support virtual wallets/currencies, through direct transactions with others with confidence and without the need for a central regulatory authority. To this end, the system designed consists of a peer-to-peer network where clients use new extensions present in the new Intel processors from the sixth generation: the Intel Software Guard Extensions. By relying on the client, which executes code in isolation on secure hardware, a more scalable and faster in the production of transactions transactional system is expected than the current traditional ones.